Review of Nation Branding Impact on Iran’s Tourism Industry development - Hamed Bozoorgkhou (International Journal of Psychosocial Rehabilitation, 2020)
As a consequence of global interaction, real time news availability, consumer generated media and content, countries have become increasingly aware of their image domestically and internationally. In response to this awareness, some countries have adopted advertising and marketing practices to manage their country image. The current study aims to develop and test a theoretical model of nation branding, which integrates the concepts of the branding and nation images. It is proposed that the overall image of the country (i.e., nation brand) is a mediator between its brand assets (i.e., internal and external assets) and tourists’ future behaviors (i.e., intentions to visit). The contribution of this paper is that, put the nation brand for the first time as a mediator role in this paper. The results confirmed that nation brand is influenced by two types of brand assets and is a critical mediator between brand assets and intention to visit.